The effects of preferred music on memory recall among Senior High School Students - San Gabriel, Trizia Arianne DC., 2017 4 0 16; 5
ABSTRACT: The purpose of this study is to know the effects of preferred music on memory recall among Senior High School students. The participants were chosen purposively, they should be a senior high school student, a student whom loves listening to music, and a student who listens to music while studying. An experimental design was used in conducting the study. There were four groups utilized - one control group and three experimental groups. Different genres were assigned to the experimental groups. All participants were given a memory recall task. Results showed that there is a significant difference between memorizing and recalling while listening to music, and memorizing and recalling with no music. The researcher concluded that music can help an individual to focus, concentrate, and avoid outside distractions.
Undergraduate Thesis: (B.S. Psychology) - Pamantasan ng Lungsod ng Maynila, 2017.
Keywords: 2 -- 0; 6; 20; 20; 2